Anatomical and cellular heterogeneity in the mouse oviduct—its potential roles in reproduction and preimplantation development. Issue 6 (9th March 2021) - Harwalkar, Keerthana; Ford, Matthew J; Teng, Katie; Yamanaka, Nobuko; Yang, Brenna; Burtscher, Ingo; Lickert, Heiko; Yamanaka, Yojiro
Abstract: The oviduct/fallopian tube is a tube-like structure that extends from the uterus to the ovary. It is an essential reproductive organ that provides an environment for internal fertilization and preimplantation development. However, our knowledge of its regional and cellular heterogeneity is still limited. Here, we examined the anatomical complexity of mouse oviducts using modern imaging techniques and fluorescence reporter lines. We found that there are consistent coiling patterns and turning points in the coiled mouse oviduct that serve as reliable landmarks for luminal morphological regionalities. We also found previously unrecognized anatomical structures in the isthmus and uterotubal junction, which likely play roles in reproduction. Furthermore, we demarcated the ampulla–isthmus junction as a distinct region. Taken together, the oviduct mucosal epithelium has highly diverse structures with distinct epithelial cell populations, reflecting its complex functions in reproduction. Abstract : The mouse oviduct mucosal epithelium has highly diverse structures with 7 distinct epithelial cell populations, likely reflecting its complex functions in reproduction.